2008
DOI: 10.1111/j.1582-4934.2008.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of nemorosone in neuroblastoma cells

Abstract: Neuroblastoma is the second most common solid tumour during childhood, characterized by rapid disease progression. Most children with metastasized neuroblastoma die despite intensive chemotherapy due to an intrinsic or acquired chemotherapy resistance. Thus, new therapeutic strategies are urgently needed. Here, we demonstrate that the novel compound nemorosone isolated from alcoholic extracts of Clusia rosea resins by reverse phase high pressure liquid chromatography (RP-HPLC) exerts cytotoxic activity in neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
3
24
0
2
Order By: Relevance
“…Moreover, in agreement with previous literature data ( Díaz-Carballo et al, 2008a), we observed that nemorosone exhibits only little toxicity in non-tumor HEK293T cells. Therefore, we believe the nemorosone acidic pK a value could be responsible for its apparent preferential toxicity on HepG2 cells, probably due to a higher proportion of the uncharged nondissociated nemorosone specie available for these cells.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, in agreement with previous literature data ( Díaz-Carballo et al, 2008a), we observed that nemorosone exhibits only little toxicity in non-tumor HEK293T cells. Therefore, we believe the nemorosone acidic pK a value could be responsible for its apparent preferential toxicity on HepG2 cells, probably due to a higher proportion of the uncharged nondissociated nemorosone specie available for these cells.…”
Section: Discussionsupporting
confidence: 94%
“…Nemorosone, a naturally occurring polycyclic polyprenylated acylphloroglucinol, has received increasing attention due to its strong in vitro anti-cancer action (Cuesta-Rubio et al, 2002;Diaz-Carballo et al, 2003, 2008aPopolo et al, 2009). Several mechanisms have been proposed to account for this action, including its ability to target the Akt/PKB signal transducer (Díaz-Carballo et al, 2008a,b) and to induce p300 histone acetyltransferase (Dal Piaz et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even more important was the global change in the physiology of these cells forced by etoposide toward acquirement of the CSC status. In addition, the analysis and validation of iCSC microRNAs isolated from 79HF6 glioblastoma cells revealed a subtle deregulation of different miRNAs such as miR204-5p known to contribute to tumor aggressiveness and metastatic behavior (Díaz-Carballo et al, 2008b;Bao et al, 2013;Qiu et al, 2013). We decided to take a descriptive rather than analytic approach to the miRNA results, as the understanding of the function of the studied representatives and this field in general is still evolving (Fig.…”
Section: Biochemical Features Of Resistant Tumor Cell Entitiesmentioning
confidence: 99%
“…Nemorosone is also effective in the management of intracranial tumors such as neuroblastomas. It mediates these anti-neoplastic effects by down-regulating N-myc levels [6]. An increase in the activity of caspase-3, and simultaneous inhibition of Akt/PKB also contributes to these anti-neoplastic effects.…”
mentioning
confidence: 99%